2021
DOI: 10.3390/metabo11010054
|View full text |Cite
|
Sign up to set email alerts
|

Two Metabolomics Phenotypes of Human Hepatocellular Carcinoma in Non-Alcoholic Fatty Liver Disease According to Fibrosis Severity

Abstract: Non-Alcoholic Fatty Liver Disease (NAFLD) is considered as the forthcoming predominant cause for hepatocellular carcinoma (HCC). NAFLD-HCC may rise in non-cirrhotic livers in 40 to 50% of patients. The aim of this study was to identify different metabolic pathways of HCC according to fibrosis level (F0F1 vs. F3F4). A non-targeted metabolomics strategy was applied. We analyzed 52 pairs of human HCC and adjacent non-tumoral tissues which included 26 HCC developed in severe fibrosis or cirrhosis (F3F4) and 26 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…A recent study found an increase in tissue BCAA level in HCC patients with severe fibrosis and cirrhosis. In 52 paired HCC tumor and nontumor tissues, BCAAs were found to be elevated in HCC tissue when compared with adjacent non-tumoral tissues [ 66 ]. The same finding was also found in another study with paired HCC tumor and nontumor tissues from 48 of their patients [ 67 ].…”
Section: Circulatory Bcaas Level As An Indicator Of a Dysmetabolic Statementioning
confidence: 99%
“…A recent study found an increase in tissue BCAA level in HCC patients with severe fibrosis and cirrhosis. In 52 paired HCC tumor and nontumor tissues, BCAAs were found to be elevated in HCC tissue when compared with adjacent non-tumoral tissues [ 66 ]. The same finding was also found in another study with paired HCC tumor and nontumor tissues from 48 of their patients [ 67 ].…”
Section: Circulatory Bcaas Level As An Indicator Of a Dysmetabolic Statementioning
confidence: 99%
“…Furthermore, both hsa‐miR‐21‐5p and PPARA levels correlated with HCC tissue markers and related with worse prognosis, reinforcing the relevance of the hsa‐miR‐21‐5p/PPARα axis in HCC and in the progression of NAFLD towards cancer. In fact, NAFLD patients with high hsa‐miR‐21‐5p presented a hepatic metabolomic profile similar to that observed in patients with HCC and NAFLD‐HCC 41,42 . These metabolic alterations indicate activation of the Warburg effect, glycolysis, nucleotide synthesis and stimulation of pentose phosphate pathway, typically overactivated in HCC, as a way to accommodate the rapid cell division of tumour cells.…”
Section: Discussionmentioning
confidence: 51%
“…Apart from the molecular aspects of hepatocarcinogenesis, the metabolic sequels of the genomic alterations also have their effect at the posttranslational level. A recent study in human [57] identified metabolites that were associated specifically with HCCs in a fibrotic or cirrhotic environment and that predominated in a pre-fibrotic environment. The majority of these changes in metabolite concentration are in all likelihood secondary to changes at the mRNA level, but choline, one of the metabolites, causes or aggravates fatty liver, while another, glutamine, is a key interorgan transporter of amino groups and a precursor to neurotransmitters.…”
Section: Discussionmentioning
confidence: 99%